STUDENTS’ ENGLISH SPEAKING DIFFICULTIES AND TEACHERS’ STRATEGIES IN ENGLISH TEACHING: A CASE STUDY AT SMA NEGERI 10 GOWA - Murti, Pramustia; Jabu, Baso; Samtidar, Samtidar (State University of Makassar, 2022)
This study aims to find out the students' English speaking difficulties at SMA Negeri 10 Gowa and then to know the teachers’ strategies used. The researcher uses a case study method through a qualitative approach. To achieve the research objectives, data were collected through questionnaires and interviews. The participants who were included in this study were twelve students from classes X and XI of SMA Negeri 10 Gowa who had met the applied criteria (purposive sampling) and three English teachers. The results of this study indicate that students have speaking problems which are divided into two types, namely psychological problem and language problem. So, the role of the teacher as a facilitator in implementing strategies to overcome student English speaking difficulties is very important based on needs. Various strategies used by teachers to improve students' English speaking skills, such as traditional method, mini dictionary, and role play. Keywords: English Speaking, student difficulties, teacher strategies used